PENENTUAN KEMUDAHAN PADA PROSES PERMESINAN ELECTRICAL DISCHARGE MACHINING - , NIDIA LESTARI; , Muslim Mahardika, S.T., M.Eng., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
All materials in the world could be formed and applied in many fields, such as aerospace, automotive, electronics, environment, and military industries. Selecting the right machining process technology will produce the suitable shape of raw material required. Electrical Discharge Machining (EDM) as one of nonconventional machine has been known by its ability in machining many complex 3D shapes even for high hardness metal. This machine could also process work piece with small size (micro machining). The ease of machining a work piece by Electrical Discharge Machining (EDM) processes is determined by ï¬ ïï± ïï² theory. A method in order to obtain the forecast model which can be used as initial prediction that made the EDM process easier by using an approach between the required energy during machining process and Î», Î¸, and Ï variables has been developed in this research. There are two methods used for establishing the formula: dimensional analysis of Buckingham Ï theorem and Logarithm-Algebra Operations. The formula chosen in this investigation is generated by Logarithm-Algebra Operations which has R2 value of 0.7477. This result shows that the percentage of formula effect on value of total energy of discharge pulses (Et) predicted is 74.77% and the effect of Mean Absolute Percentage Error (MAPE) formula on value of total energy of discharge pulses (Et) predicted is 30.32%. Material which has the lowest value calculated using 0,2156 0,7 0,2537 E ï»ï¬ ïï± ïï² formula is the material that is predicted will be the easiest to be machined so that the suitable electrodes could be determined. The suitable electrodes will reduce the energy needed during machining and the tool electrode wear